Painful and sometimes deadly experiments which Nazi doctors carried out on children - Weindling, Paul (Acta Paediatrica, 2022)
Coerced human experiments are among the most disturbing forms of ethical violations and criminality in medicine under National Socialism. Until 2016, there was no evidence‐based analysis concerning numbers of victims and the type of experiments. A reference resource on Victims of Biomedical Research under NS. Collaborative Database of Medical Victims currently covers 28 655 victims who were subjected to 359 different experiments by the Nazis during World War Two. Drawing on this resource, this paper focuses on research on children. Finally, the narrow focus on the experiments, highlighting scientific methodology but disregarding the killing procedures of the Holocaust, is critically analysed.